Building integrated solar thermal collectors for heating & cooling applications - Buker, Mahmut Sami (2015)
International Energy Agency Solar Heating & Cooling (IEA SHC) programme states the fact that space/water heating and cooling demand account for over 75% of the energy consumed in single and multi-family homes. Solar energy technology can meet up to 100% of this demand depending on the size of the system, storage capacity, the heat load and the region’s climate. Solar thermal collectors are particular type of heat extracting devices that convert solar radiation into thermal energy through a transport medium or flowing fluid. Although hybrid PV/T or thermal-alone systems offer some advantages to improve the solar heat utilisation, there are a few technical challenges found in these systems in practice that prevented wide-scale applications. These technical drawbacks include being expensive to make and install, inability of switching already-built photovoltaic (PV) systems into PV/T systems, architectural design etc. The aims of this project, therefore, were to investigate roof integrated solar thermal roof collectors that properly blend into surrounding thus avoiding ‘add on’ appearance and having a dual function (heat absorption and roofing). Another objective was to address the inherent technical pitfalls and practical limitations of conventional solar thermal collectors by bringing unique, inexpensive, maintenance free and easily adaptable solutions. Thus, in this innovative research, unique and simple building integrated solar thermal roof collectors have been developed for heating & cooling applications. The roof systems which mainly based on low cost and structurally unique polyethylene heat exchanger are relatively cost effective, competitive and developed by primarily exploiting components and techniques widely available on the market. The following objectives have been independently achieved via evaluating three aspects of investigations as following: • Investigation on the performance of poly heat exchanger underneath PV units • Investigation on the performance of a Building Integrated PV/T Roof ‘Invisible’ Collector combined with a liquid desiccant enhanced indirect evaporative cooling system • Investigation on the build-up and performance test of a novel ‘Sandwich’ solar thermal roof for heat pump operation These works have been assessed by means of computer simulation, laboratory and field experimental work and have been demonstrated adequately. The key findings from the study confirm the potential of the examined technology, and elucidate the specific conclusions for the practice of such systems. The analysis showed that water temperature within the poly heat exchanger loop underneath PV units could reach up to 36°C and the system would achieve up to 20.25% overall thermal efficiency. Techno-economic analysis was carried out by applying the Life Cycle Cost (LCC) method. Evaluations showed that the estimated annual energy savings of the overall system was 10.3 MWh/year and the cost of power generation was found to be £0.0622 per kWh. The heat exchanger loop was coupled with a liquid desiccant enhanced indirect evaporative cooling unit and experimental results indicated that the proposed system could supply about 3 kW of heating and 5.2 kW of cooling power. Lastly, the results from test of a novel solar thermal collector for heat pump operation presented that the difference in water temperature could reach up to 18°C while maximum thermal efficiency found to be 26%. Coefficient Performance of the heat pump (COPHP) and overall system (COPSYS) averages were attained as COPHP=3.01 and COPSYS=2.29, respectively. An economic analysis pointed a minimum payback period of about 3 years for the system.